DISCIPLINE CHARACTER AT PANCA BUDI MEDAN MIDDLE SCHOOL - Syauqky Khalis Nasir; Tengku Cut Afifah; Tia Ramadani; Rizki Sakinah; Nur Oktaviani; Kamil (Alhamdulillah : Jurnal Agama Islam, 2026)
Discipline is one of the main pillars of character formation that is a serious concern in the world of education, especially at the Junior High School (SMP) level where students are in their early adolescence and are vulnerable to rule violations. School rules serve as a legal and pedagogical instrument to regulate student behavior while instilling disciplinary values. This study uses a descriptive qualitative approach with a case study type. Data collection techniques were carried out through participatory observation, in-depth interviews with the principal, vice principal for student affairs, guidance and counseling teachers, homeroom teachers, students, as well as documentation of rules, violation logbooks, and discipline development programs. The results of the study indicate that the implementation of student rules of conduct at Panca Budi Medan Middle School was carried out through three main stages: (1) the socialization stage, namely the introduction and explanation of the rules of conduct to all students at the beginning of the school year; (2) the enforcement stage, namely the application of sanctions consistently and proportionally according to the level of violation; and (3) the coaching stage, namely coaching and mentoring efforts for students who violate so that they do not repeat their violations. The rules of conduct at Panca Budi Middle School Medan cover three main areas: religious rules (congregational prayer, Al-Quran recitation, and other religious activities), academic rules (attendance, completing assignments, and taking exams), and social behavior rules (dressing, speaking, and interacting with teachers and friends).